The Distribution, Similarity, and Conservation Status of the Amphibians and Reptiles of the Biogeographic Provinces of Northwestern Mexico - Julio A. Lemos-Espinal; Geoffrey R. Smith (Diversity)
The herpetofaunal diversity of northwestern Mexico, encompassing the Californian, Baja California, and Sonoran Desert biogeographic provinces, is characterized by relatively low species richness but a high degree of endemism. This region, particularly the islands of the Gulf of California, is recognized as a biodiversity hotspot. However, amphibian and reptile species in this area, especially those on the Gulf islands, are facing significant threats to their survival, including non-native species, habitat loss, and climate change. These factors pose considerable challenges to their conservation. In this study, we compiled updated lists of amphibian and reptile species across these three provinces, assessed their conservation status, identified the threats they face, and compared them with those in neighboring biogeographic provinces. Our analysis recorded a total of 228 species, comprising 29 amphibians and 199 reptiles, with a notable proportion of endemics, particularly in Baja California. Amphibians, due to the region’s arid conditions, are underrepresented and generally face a lower level of conservation concern. In contrast, reptiles, especially those on the islands, are at higher risk, primarily due to habitat loss, invasive species, and climate change. Of the 228 species, one amphibian and 21 reptiles are classified in a category of conservation concern (Vulnerable, Endangered, Critically Endangered) by the International Union for Conservation of Nature (IUCN) Red List. In addition, 47 species (one amphibian and 46 reptiles) are listed as threatened (A) or at risk of extinction (P) by the Secretaría del Medio Ambiente y Recursos Naturales (SEMARNAT). These findings emphasize the urgent need for conservation strategies, particularly for island reptile species, that involve collaboration among scientists, local communities, and federal and state authorities to address these threats and safeguard the region’s herpetofauna. Similarity analysis revealed significant ecological connectivity among the amphibian and reptile communities across the three provinces. The similarity in species between the Californian, Baja California, and Sonoran Desert provinces highlights the role of historical climatic events, geographic barriers, and ecological factors in shaping species distributions of amphibians and reptiles in northwestern Mexico.